2016
DOI: 10.1097/scs.0000000000002675
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Submental Artery Perforator Island Flap Without Including Digastric Muscle in the Reconstruction of Lower Face and Intraoral Defects

Abstract: The submental artery perforator island flap without including the digastric muscle is a reliable and suitable option for the medium-sized defects in the lower face and intraoral defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The major advantages of submental artery flaps are the well-camouflaged scar lines, minimal donor site morbidity, satisfactory color and contour matches, favorable mobility due to a wide rotational arch, short surgical time, and reliability. 18 Many institutions' experiences have led to the conclusion that the cost of head and neck microsurgical reconstruction is higher than that of locoregional methods, and our experience supports this argument. There are several factors that contribute to the higher cost: prolonged surgical time, the need for sophisticated instrumentation, and prolonged hospitalization for flap monitoring.…”
Section: Discussionsupporting
confidence: 72%
“…The major advantages of submental artery flaps are the well-camouflaged scar lines, minimal donor site morbidity, satisfactory color and contour matches, favorable mobility due to a wide rotational arch, short surgical time, and reliability. 18 Many institutions' experiences have led to the conclusion that the cost of head and neck microsurgical reconstruction is higher than that of locoregional methods, and our experience supports this argument. There are several factors that contribute to the higher cost: prolonged surgical time, the need for sophisticated instrumentation, and prolonged hospitalization for flap monitoring.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, although several modifications have been developed of the submental island, none of the modifications has included a vertical component. [7][8][9][10][11][12] This vertically oriented flap provides for straight line linear closure in the midline of the neck, which in the present case, aided in reestablishing the cervicomental angle, normalizing the cervical contour, and improving donor site cosmesis. Moreover, given our patient's previous ablative and reconstructive procedures, the vertical orientation allowed for direct access to nearly the full length of the pectoralis major muscle flap, which, after debulking and recontouring, further facilitated cervical recontouring.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, several modifications of this procedure have been developed, although none have included a vertical island flap. [7][8][9][10][11][12] We describe a novel variation using a vertically based submental island flap for maxillary reconstruction in a patient with significant coronary and peripheral arterial disease that prohibited microvascular reconstruction. The diamond-shaped flap was inset along the long axis of the maxillary arch with resulting straight line linear closure in the neck and optimized esthetics of the donor site.…”
mentioning
confidence: 99%
“…26 While select case series have reported excellent outcomes with perforator-based techniques, incorporating both the digastric and mylohyoid muscles as a barrier of protection for the distal pedicle and cutaneous perforators likely provides the highest level of flap consistency and reliability. 19,21,26 Conversely, in studies excluding the mylohyoid, several have reported total flap failure up to 10% and partial flap necrosis over 20%. 6,12,13,15 These figures are important and must be kept in mind as the field of head and neck reconstruction shifts focus from free tissue to regional flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports, however, continue to recommend dissection of the distal pedicle off the mylohyoid, and in some cases, dissection of the cutaneous perforator to leave the anterior belly of digastric in situ. 6,7,12,15,16,[20][21][22] While such approaches may be successful in experienced hands, inclusion of the mylohyoid is likely to provide more universal reliability among reconstructive surgeons. 19 An important gap in the available literature, however, is the specific technical steps required to safely and proficiently include the mylohyoid into the submental island flap harvest.…”
Section: Introductionmentioning
confidence: 99%